MicroRNAs, transforming growth factor beta‐1, and tissue fibrosis. (29th November 2012) - Bowen, Timothy; Jenkins, Robert H; Fraser, Donald J
Abstract: MicroRNAs are short noncoding RNA regulators that repress synthesis of their targets post‐transcriptionally. On average, each microRNA is estimated to regulate several hundred protein‐coding genes, and about 60% of proteins are thought to be regulated by microRNAs in total. A subset of these genes, including the key profibrotic cytokine transforming growth factor beta‐1 (TGF‐β1), exhibits particularly strong levels of post‐transcriptional control of protein synthesis, involving microRNAs and other mechanisms. Changes in microRNA expression pattern are linked to profound effects on cell phenotype, and microRNAs have an emerging role in diverse physiological and pathological processes. In this review, we provide an overview of microRNA biology with a focus on their emerging role in diseases typified by organ fibrosis.